EDUKASI PENGGUNAAN OBAT ANTIBIOTIK YANG BAIK DAN BENAR TERHADAP MASYARAKAT DI NAGARI SIPINANG PALEMBAYAN KABUPATEN AGAM - Noverial Noverial; Yohannes Alen; Dwisari Dillasamola (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2023)
Antibiotic resistance is a problem that arises in the community due to the high use of antibiotics inappropriately. The problem arises because of the lack of understanding of the community regarding the handling and use of antibiotic drugs. Microorganisms that have been resistant to antibiotics when given the same antibiotic, it cannot kill the microorganisms that are the target of this can cause antibiotic resistance. Therefore, the purpose of this activity is to provide knowledge and understanding to the community regarding the wise and good use of antibiotics to prevent drug resistance. This community education activity was carried out in nagari Sipinang, Palembayan District, Agam Regency, West Sumatra, with lecture education methods and open discussions with the community. Based on the results obtained, the community was very enthusiastic about this education and counseling activity and opened public knowledge related to antibiotic resistance. This community education activity was carried out in nagari Sipinang, Palembayan District, Agam Regency, West Sumatra, with lecture education methods and open discussions with the community. Based on the results obtained, the community was very enthusiastic about this education and counseling activity and opened public knowledge related to antibiotic resistance. This activity is expected to be a means for the community to use antibiotics wisely and well in the use of appropriate, accurate, and effective. In addition, this activity is also expected to provide the community with sufficient information to be wiser in obtaining and using antibiotics so that people are not afraid of antibiotic resistance if their use has been carried out properly and wisely. This activity is important because of the lack of information obtained by the community in Nagari Sipinang regarding the use of antibiotics so that this educational activity will also make people more concerned with health.